Evaluation of the factors affecting the necessity for revision surgery in choanal atresia. (December 2021) - Aydemir, Levent; Sen, Comert; Kara, Hakan; Pamuk, Saim; Kesimli, Mustafa Caner; Comoglu, Senol; Keles Turel, Meryem Nesil
Abstract: Objective: This study aims to compare the effects of different surgical techniques for congenital choanal atresia (CCA), and particular emphasis is given to the analysis of the factors affecting the surgical outcome. The necessity for revision surgery and surgical outcomes were retrospectively investigated in patients undergoing revision surgery according to a recently proposed classification system. Material and method: A retrospective study was conducted on patients operated for CCA between January 2007 and December 2018 at a university hospital. Data in the medical records, including patient age when the initial surgery was performed, gender, additional anomalies and medical conditions, the duration of gestation, side and type of atresia, type of surgery and need for revision surgery were reviewed. Results: Forty-five patients treated for CCA in our university hospital were screened. The mean follow-up duration was 82.16 months. Revision surgery was required in 9 of 26 cases, which are included in the study (34.6%). Fourteen patients presented with bilateral CCA, while 12 were unilateral cases. Sixteen patients (61.5%) had comorbid medical conditions. While the removal of vomer and mucoperiosteal flap use affects successful surgical repair, no differences were observed in choanal atresia type, laterality, use of stent and the presence of additional medical conditions. Conclusion: The most important factors affecting surgical success for CCA are the removal of the vomer and closure of all bare bone tissues using a mucoperiosteal flap. Use of stents provides no additional benefit, apart from preventing synechiae formation.